“Supermaids”: Hyper-resilient Subjects in Neoliberal Migration Governance - Chee, Liberty (International political sociology, 2020)
Abstract Resilience is a concept in world politics that emerged as a way to respond to the impossibility of guaranteeing security in an era of complexity. Without a central authority to provide security, risk is devolved to the individual. Those who cannot secure themselves are enjoined to constantly adapt to the unknown. Where control over complex systems is now thought to be impossible, the path to managing risks is through self-control. This paper demonstrates how such a subject is produced, and indeed whose production, I argue, is crucial to the functioning of a global labor market that is governed “without government.” Migrant domestic workers acutely instantiate the kind of human subjectivity called forth by neoliberalism—a “resilient subject.” The paper describes how this ideal worker is produced through resilience training in various stages of the migration trajectory—during recruitment, training prior to deployment, and while on their overseas residency. This paper demonstrates how managing the insecurities of migrant domestic work means working on the “self” rather than addressing gaps in legal or regulatory mechanisms. In resilience training, the worker becomes the necessary component of neoliberalism as a governmental rationality, one that is enjoined to transform risk into opportunity.